Social, economic and productive profile of family farmers in the semi-arid of Ceará (Research, Society and Development, 2024)
Family farming is of vital concern to the economy of the state of Ceará. Being responsible for the supply of food for the local market, sustainability and profitability of the family producer, it can be highlighted as one of the fastest growing sectors in food production and raising animals, stimulating the socioeconomic development of small regions, through the generation of jobs and income distribution. Therefore, the objective of this study was to analyze the social, economic and productive profile of family farming in the semi-arid state of Ceará. A quantitative study was held, based on the application of a questionnaire through interviews. The study was carried out in communities and settlements, in family-type units, dedicated to animal production. Fifty-seven interviews were recorded in the cities of Umirim and Tururu, in Ceará. The results showed that 53% of the interviewees correspond to the male sex. In addition, cattle was the main profitable activity, being developed by 56.2% of the producers, followed by the agricultural activity, practiced by 43.8% of the interviewees. The data showed the productive diversity of the properties, with emphasis on the sale of milk (10.5%), beef (28%), pork (35%) and vegetables (16%) for local trade. However, 35.1% of producers do not have their own. In this context, family farming has a close relationship with the promotion of the economy, but also of subsistence, making it possible to conclude that family farming needs strategies for the development of rural activities.